Estonian book historiography - Mare Lott (Knygotyra)
he scientific study of the history of the Estonian book began in the 1930s, and some essays published then have not lost their value up to the present. During this period, the fundamentals of book statistics and the first comprehensive history of the Estonian book by F. Puksoo were published. The attention of researchers was mainly concentrated on 16th-17th, and partly 18th-century publications.